Equine influenza - BOUNTOURI (Μ. ΜΠΟΥΝΤΟΥΡΗ), M.; FRAGKIADAKI (Ε. ΦΡΑΓΚΙΑΔΑΚΗ), E.; DAFIS (Β. ΝΤΑΦΗΣ), V.; XYLOURI (Ε. ΞΥΛΟΥΡΗ), E. (Journal of the Hellenic Veterinary Medical Society, 2017)
Equine Influenza (ΕΙ) is an acute, highly contagious, respiratory disease of equine. The causative agent of EI infections is a type A influenza virus, classified into the family Orthomyxovirìdae. Up to today two subtypes of EI are known, subtype 1 (H7N7) and subtype 2 (H3N8). Subtype 1 has not been isolated since 1977 and is presumed that has been replaced by the subtype 2, which is the causative agent of many recent outbreaks. Antigenic drift of H3N8 viruses resulted in the divergence of strains into two distinct evolutionary lineages, which co-circulate. The high morbidity of equine influenza disease was demonstrated in all resent widespread outbreaks all over the world. On the other hand, the mortality rate of influenza disease in equids is generally low, unless secondary bacterial infections occurred. Devastating economic loss of the disease in breeding and race animals reinforced the importance of vaccination. Despite the extensive use of vaccines, outbreaks of equine influenza continue to occur. In 2003 there were widespread outbreaks of equine influenza among un vaccinates and regularly vaccinated horses in Europe and later all over the world, even in regions that rarely report equine influenza outbreaks. However, studies have shown that vaccination does not prevent transmission and on the other hand multiple booster doses could result to paralysis of the immune system. Furthermore, all these developments including transmission to swine and dogs, shows the unpredictable evolutionary pathways the equine influenza virus follows. In conclusion, influenza surveillance and research should go on and provide useful tools to better evaluate when vaccine strains should be updated.